Species Richness And Feeding Guilds Of Bird Communities In The Patuguran-Pasuruan Mangrove Area Estuary - Dwi Oktafitria; Satriyo, Roso; Anggraini, Widi Meisya; Surya Muchamad, Lutfi; Restiningsih, Restiningsih (UNIVERSITAS PGRI MADIUN, 2025)
The existence of the Patuguran mangrove estuary area which is currently a great potential in the development of ecotourism can be a threat to the diversity of bird species that exist so that this study was conducted with the aim of knowing the richness of bird species and types of plant-eating bird communities in the Patuguran mangrove area of Pasuruan Regency which is expected that this estuary area is able to support the existence of birds with high diversity. Bird data collection was carried out in October 2024 using the point count method at 2 location points in the estuary area and the middle of the Patuguran Mangrove Area and data analysis using the Margalef species richness index. The results showed that the species richness index (R) value was 4.63 which was included in the high species richness category, while the feeding guild type of the bird community found was 8 species, namely Insectivores (33%), Carnivores and Insectivores (24%), Carnivores (15%), Fragivores (9%), Granivores (9%), Insectivores and Fragivores (3%), Nectivores (3%), and Omnivores (3%).